Development of a wall jet model dedicated to 1D combustion modelling for CI engines - Alejandro Aljure Osorio (SAGE Publishing, 2021)
Diesel engines are becoming smaller as technology advances, which means that the fuel spray (or jet) interacts with the cylinder walls before combustion starts. Most fuel injection 1D models (especially for diesel fuel) do not consider this interaction. Therefore, a wall-jet sub-model was created on an Eulerian 1D diesel spray model. It was calibrated using data from the literature and validated with experimental data from a fuel spray impacting a plate in a constant volume combustion chamber. Results show that the spray moving along the wall has a higher mixing rate but less penetration as an equivalent free jet, therefore they show a similar volume. Spray-wall interaction creates a stagnation zone right before the impact with the wall, and friction of the jet with the wall is relatively low. All these phenomena are well captured by the wall-jet sub-model.